The Relevance of Inequality Research in Sociology for Inequality Reduction - Thomas A. DiPrete; Brittany N. Fox-Williams (Socius, 2021)
Social inequality is a central topic of research in the social sciences. Decades of research have deepened our understanding of the characteristics and causes of social inequality. At the same time, social inequality has markedly increased during the past 40 years, and progress on reducing poverty and improving the life chances of Americans in the bottom half of the distribution has been frustratingly slow. How useful has sociological research been to the task of reducing inequality? The authors analyze the stance taken by sociological research on the subject of reducing inequality. They identify an imbalance in the literature between the discipline’s continual efforts to motivate the plausibility of large-scale change and its lesser efforts to identify feasible strategies of change either through social policy or by enhancing individual and local agency with the potential to cumulate into meaningful progress on inequality reduction.